2022
DOI: 10.1097/sla.0000000000005496
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interventions and Outcomes in Civilian and Military Isolated Gunshot Wounds to the Head

Abstract: Objective: The purpose of this study was to compare therapeutic strategies and outcomes, following isolated gunshot wounds of the head, between military and civilian populations. Background: Recent military conflicts introduced new concepts in trauma care, including aggressive surgical intervention in severe head trauma. Methods: This was a cohort-matched study, using the civilian Trauma Quality Improvement Program (TQIP) database of the American College of Surgeons (ACS) and the Department of Defense Trau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Additional studies have shown the time-critical nature of these injuries and need for expert neurosurgical intervention; these are not cases that can be safely “stabilized and evacuated” to Role 4 or 5 (Fig. 1) facilities with neurosurgical capabilities 7,8 . A commonly proffered solution or stopgap measure has been to have general or trauma surgeons perform emergent decompressive cranial surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies have shown the time-critical nature of these injuries and need for expert neurosurgical intervention; these are not cases that can be safely “stabilized and evacuated” to Role 4 or 5 (Fig. 1) facilities with neurosurgical capabilities 7,8 . A commonly proffered solution or stopgap measure has been to have general or trauma surgeons perform emergent decompressive cranial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1) facilities with neurosurgical capabilities. 7,8 A commonly proffered solution or stopgap measure has been to have general or trauma surgeons perform emergent decompressive cranial surgery. This approach ignores the available literature and experience and represents a form of magical thinking that must be removed from modern military medical planning.…”
Section: Discussionmentioning
confidence: 99%